Air Pincuran Balai Ateh: Warisan Kearifan Lokal sebagai Penunjang Ketahanan Air Masyarakat Nagari Situmbuk - Prima Yoselina; Kheniva Diah Anggita; Metha Kemala Rahayu (CV. ITTC INDONESIA, 2026)
Clean water is a basic need that is very important for the health and welfare of the community. However, access to clean water is still a challenge for some people in Nagari Situmbuk due to the limitations of piped water services and geographical conditions that do not support the development of independent water sources. This community service activity aims to identify the use of Balai Ateh Pincuran Water as the main source of water for the community and increase public awareness about the importance of safe and sustainable management and utilization of clean water. The activity was carried out for 25 days in Nagari Situmbuk with field observation methods, interviews, discussions with the community, and education about sanitation and clean water use. The target of the activity includes people who use the Balai Ateh Pincuran Water for their daily needs. The results of the activity show that Air Pincuran Balai Ateh has a very important role in meeting the domestic needs of the community, such as cooking, bathing, washing, and cleaning houses, as well as supporting the needs of public facilities such as mosques, schools, and government offices. However, there are still people who have not used the water as drinking water due to concerns about its quality and cleanliness. Through this service activity, the community gained an understanding of the importance of maintaining the quality of water sources, the application of good sanitation, and as an alternative to simple water treatment before consumption. These efforts are expected to support the availability of clean water that is safe, sustainable, and easily accessible to all Nagari Situmbuk communities.